ANALISIS SEBARAN TUTUPAN VEGETASI MENGGUNAKAN CITRA LANDSAT 8 DI KAWASAN HUTAN PENDIDIKAN UNIVERSITAS TADULAKO - Balqish Balqish; Akhbar Akhbar; Ida Arianingsih (Universitas Tadulako, 2022)
Educational Forest is an education medium which has purpose to support and increase the education quality about the introduction and function of forest. An important information is needed in order to manage the Educational Forests it was the vegetation distribution in the forest. By determining Tadulako University Education Forest as a forest with specific purpose in limited production forest region which is located in Donggala Regency, Central Sulawesi Province as wide as ± 1.813 hectare as the training and education forests since August, 26th 2016 (SK.661/MenLhk/Setjen/PLA.O/8/2016) and no research has been conducted about vegetation distribution, therefore it needs to do a research in order to analyze the vegetation distribution by using descriptive method in unsupervised classification to obtain the data by using Citra Landsat 8 and ArcGis 10.0 software, and field survey method to obtain the data in Educational Forests. The results of vegetation distribution by using Citra Landsat 8 which is recorded in 2017 path/row 114/61 in Educational Forest, obtained results that the vegetation distribution in Tadulako University Education Forests has width ± 1.813 ha which is dominated by forest wide as 1.137,26 ha (62,71 %) with distribution pattern randomly and evenly. The others vegetation distribution are shrubs as wide as 641,20 ha (35,36 %) and cloud cover as wide 39,66 ha (1,94 %). The results of the vegetation distribution map analysis in this research has accuracy rate of 86,11 %, it means that the vegetation distribution map fulfill the standards of accuracy interpretation and can be used appropriately in order to know the vegetation distribution in Tadulako University Education Forests